Integrating Local Tourism into Instructional Material Design to Improve Narrative Writing Skills in Elementary Learners - Ramadhani, Annisa; Hookeriana, Raya Vanda; Septriansyah, Yega Kusmi (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
This research aims to develop a narrative writing teaching material based on the local tourism of Kaur Regency for elementary school students, as well as to determine its validity, effectiveness, and practicality. The development process employed the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The research subjects included expert validators, teachers, and fourth-grade elementary school students. The instruments used were expert validation sheets, narrative writing performance tests (pretest–posttest), and response questionnaires for students and teachers.The results show that the developed teaching material achieved a very high level of validity, with an average score of 87.67% as assessed by material, language, and media experts. In terms of effectiveness, students’ narrative writing ability improved significantly, as indicated by an N-Gain score of 0.48, classified as a moderate category, confirming that the teaching material is effective in enhancing students’ writing skills. Regarding practicality, the teaching material received highly positive responses from both students (92%) and teachers (90%), indicating that it is easy to use, engaging, and supportive of classroom learning activities.Overall, the findings conclude that the narrative writing teaching material based on Kaur Regency’s local tourism is valid, effective, and practical for use in elementary school instruction. Integrating local tourist destinations into the learning process has been shown to increase students’ motivation and narrative writing skills while supporting contextual learning in elementary education.